Ontología y Procesamiento de Lenguaje Natural - Moreno, Denis Cedeño; Lombardo, Miguel Vargas (KnE Engineering, 2018)
At present, the convergence of several areas of knowledge has led to the design and implementation of ICT systems that support the integration of heterogeneous tools, such as artificial intelligence (AI), statistics and databases (BD), among others. Ontologies in computing are included in the world of AI and refer to formal representations of an area of knowledge or domain. The discipline that is in charge of the study and construction of tools to accelerate the process of creation of ontologies from the natural language is the ontological engineering. In this paper, we propose a knowledge management model based on the clinical histories of patients (HC) in Panama, based on information extraction (EI), natural language processing (PLN) and the development of a domain ontology. Keywords: Knowledge, information extraction, ontology, automatic population of ontologies, natural language processing.